Simulation and implementation results of a 3-phase 4-wire shunt active power filter - Pregitzer, Ricardo G. (2006)
This paper presents a laboratory prototype of a 3-phase 4-wire Shunt Active Power Filter used to compensate the source currents in an electrical system. The controller, based on the well known p-q theory was implemented on a DSP and determines the reference currents to be generated by a 2-level inverter. Some experimental results are presented and compared with computer simulations obtained with EMTDC/PSCAD V4.2. Other simulation results that demonstrate some of the improvements that will be made to the implemented prototype are also presented.